Adsorption and Corrosion Inhibition of Mild Steel in Acidic Media by Expired Pharmaceutical Drug - S. Khalifa , A. AL-abbassi; M. Suliman (Journal of Pure & Applied Sciences, 2019)
The effectiveness of the anti-Assam Theophylline (TD), expired drug, as corrosion inhibitor for mild steel in 0.5M HCl was investigated by weight loss method. Data obtained from weight loss studies were analyzed, and the Results show that the used TD drug was a good inhibitor. The inhibition efficiency increases with increasing the concentration of TD inhibitor and reached a maximum value of 73% at 30 OC and 100 ppm of the used inhibitor. The adsorption isotherm of TD obeyed Langmuir and Temkin adsorption isotherm. Quantum chemical calculations based on denisity function theory, DFT, were performed on TD drug. Calculated parameters such as the highest occupied molecular orbital energy (EHOMO), the lowest unoccupied molecular orbital energy (ELUMO), energy gap (?E), dipole moment (µ), electronegativity (?), electron affinity (A), global hardness (?), softness (?) and ionization potential (I), were calculated and correlated to the experimental data.